(untitled) (International Journal of Physiotherapy, 2016)
Background: Miller-Fisher syndrome (MFS) is characterized by gait ataxia, external ophtalmoplegia and areflexia and thought as an uncommon variant of Guillain Barre syndrome. Miller-Fisher syndrome is observed in about 5-8% of all Guillain Barre syndrome (GBS) cases. In MFS patients, spontaneous improvement was observed in the first 3 months and these improvements were started by the 2nd week. Methods: This case was referred to physiotherapy and rehabilitation program at the 4th week since the appropriate medical treatments were unsuccessful after the attack. The patient was evaluated generally before physiotherapy program, and muscle length, strength loss, deep tendon reflexes, postural impairments and daily difficult activities and positions were assessed. Besides, the desired daily activities were identified by The Canadian Occupational Performance Measure (COPM). Treatment program was adjusted according to the patient and changes during treatment period were observed. Physiotherapy program included classical physiotherapy methods: posture correction, correction of short muscles, muscle strengthening, flexibility increase, balance/coordination, sitting and standing functions and walking improvement and climbing up stairs. Results: After the treatment, lower extremity muscle shortness decreased and muscle strength, standing on one foot duration, independent walk speed increased in time. Before treatment, he could not climbing upstairs, but it was achieved 1 year after the treatment. Berg balance score increased in time and his most desired activities by COPM (10/10) were could be performed after the treatment. Conclusion: The case improved with physiotherapy and rehabilitation program gradually with years.In the treatment of MFS patients, physiotherapy and rehabilitation being part of the treatment will be useful.